Biosynthesized silver nanoparticles prevent bacterial infection in chicken egg model and mitigate biofilm formation on medical catheters - Pradhan L.; Sah P.; Nayak M.; Upadhyay A.; Pragya P.; Tripathi S.; Singh G.; Mounika B.; Paik P.; Mukherjee S. (My University, 2025)
Investigating the application of innovative antimicrobial surface coatings on medical devices is an important field of research. Many of these coatings have significant drawbacks, including biocompatibility, coating stability and the inability to effectively combat multiple drug-resistant bacteria. In this research, we developed an antibiofilm surface coating for medical catheters using biosynthesized silver nanoparticles (b-Cs-AgNPs) developed using leaves extract of Calliandra surinamensis. Various characterization techniques were employed to thoroughly characterize the synthesized b-Cs-AgNPs and c-AgNPs. b-Cs-AgNPs were compatible with human normal kidney cells and chicken embryos. It did not trigger any skin inflammatory response in in vivo rat model. b-Cs-AgNPs demonstrated potent zone of inhibition of 19.09 mm when subjected to the disc diffusion method in E. coli confirming strong antibacterial property. Different anti-bacterial assays including liquid growth curve, colony counting assay, biofilm formation assay supported the potent antimicrobial efficacy of b-Cs-AgNPs alone and when coated to medical grade catheters. Mechanistic studies reveal the presence of ferulic acid, that was important for the synthesis of b-AgNPs along with enhanced antibacterial effects of b-Cs-AgNPs compared to c-AgNPs, supported by molecular docking analysis. These results together demonstrated the effective role b-Cs-AgNPs in combating infections and mitigating biofilm formations, highlighting their need for further study in the field of biomedical applications. Graphical abstract: Schematic Illustration of Eco-Friendly Synthesis for Biofilm Prevention on Medical Catheters and Bacterial Infection Mitigation. Created with BioRender.com. (Figure presented.) © The Author(s), under exclusive licence to Society for Biological Inorganic Chemistry (SBIC) 2024.